DETERMINATION OF CAREER STRESS OF THE STUDENTS WHO RECEIVE TOURISM EDUCATION: A RESEARCH ON THE STUDENTS OF GIRESUN UNIVERSITY - Eray TURPCU (Fırat University, 2019)
In today's education and business life relation, the stress regarding what to do after taking the diploma is an important issue for students who are continuing their education. This stress factor which begins at the university preference stage continues throughout the education life. Determining student perceptions related to career stresses for the future will make it easier to find solutions which will provide opportunities to reduce sources of the stress. The aim of this study is to determine the career stresses of undergraduate and associate degree students who are receiving tourism education at Giresun University Bulancak Kadir Karabas School of Applied Sciences and Social Sciences Vocational School. The study is important with respect to determining the career stresses of the students during their education life and providing solution. In accordance with this purpose, 223 students were asked questions regarding their career expectations and concerns through face-to-face questionnaire method. Data acquired with the questionnaire were analyzed with SPSS 21.0 package program. While the data were being analyzed, frequency and percentage distribution was carried out in interpreting the demographic expressions of the students and exploratory factor analysis was performed in order to determine the dimensions that the perceptions related to career stress have and provide the validity of the scale. In order to test the differences related to demographic characteristics of the obtained dimensions, the t-test was used for binary variables and the analysis of variance was used for three or more variables. Findings that were acquired in the research revealed that the biggest concern of the students regarding their career stress was job finding, followed by career uncertainty and lack of knowledge which were the second most important stress sources and the third important stress factor was the external conflict dimension.